Epixylic microbial communities as key regulators of methane emissions from submerged wood in a tropical hydroelectric reservoir - Fanny Colas; Léa Cabrol; Jean‐Marc Baudoin; Yves Prairie; Jacques Beauchêne; Vincent Chanudet; Etienne Dambrine; Sophie Guasco; Frederick Jacob; Arthur Szylit; Corinne Valette; Régis Vigouroux; et al. (Limnology and Oceanography, 2026)
Tropical hydroelectric reservoirs are recognized hotspots for greenhouse gas emissions, yet the role of submerged forests in these emissions remains poorly understood. In this study, we investigated the contribution of standing dead trees and their associated epixylic biofilms to methane (CH 4 ) and carbon dioxide (CO 2 ) emissions in the permanently stratified Petit Saut reservoir, French Guiana. We conducted in situ measurements of greenhouse gas fluxes from submerged trunks at multiple depths using static chambers. To unravel the microbial mechanisms underlying CH 4 dynamics, we characterized the active microbial communities and quantified methane production and oxidation rates in both wood and biofilm samples collected above and below the oxycline, using 16S rRNA sequencing and laboratory incubations. Our findings revealed that submerged wood serves as an unrecognized source of in situ CH 4 production, primarily via acetoclastic methanogenesis dominated by Methanosaeta . In contrast, epixylic biofilms acted as effective CH 4 sinks, with methane oxidation largely driven by Methylocystis . Microbial composition and activity showed strong vertical stratification, closely linked to oxygen availability. In situ fluxes mirrored these microbial patterns, with net CH 4 and CO 2 efflux observed below the oxycline and net influx above it. This study highlights the dual role of submerged wood and its surface biofilms in CH 4 cycling, emphasizing the importance of microbial interactions in regulating greenhouse gas emissions from flooded tropical forests. These findings underscore the need to include wood‐mediated processes in greenhouse gas budgets of tropical reservoirs, especially as dam construction continues to expand in forested tropical regions.

A simple approach to quantifying whole‐lake methane ebullition and sedimentary methane production, and its application to the Canadian Lake Pulse dataset - Jihyeon Kim; Shoji D. Thottathil; Yves T. Prairie (Limnology and Oceanography, 2025)
Aquatic sediments represent a key component for understanding CH 4 dynamics and emission to the atmosphere. Once produced in the sediments, CH 4 is released either by diffusion at the sediment–water interface or by bubbling out to the atmosphere when total gas pressure in the sediment exceeds local ambient pressure due to high CH 4 production. Although bubbling is one of the dominant CH 4 emission pathways in lakes, direct measurements of this flux are hampered by its high spatiotemporal variability and methodological limitations. Here, we develop a conceptual approach to quantify CH 4 production in lake sediments and particularly its release as bubbles based on simple measurements of bubble gas content and depth. Its main assumptions were empirically tested using > 200 long‐term bubble trap deployments collected from 4 temperate lakes. We then applied the developed methodology to a suite of 408 Canadian lakes to produce the first standardized large‐scale assessment of lakes CH 4 ebullitive flux during summer. Our results show that lake sediments produced CH 4 at a median rate of 3.3 mmol m −2 d −1 (ranged from 0.2 to 11.8 mmol m −2 d −1 ), releasing 33% via ebullition to the atmosphere. These rates are remarkably similar in magnitude to other regional estimates in the literature. Moreover, our approach revealed that catchment slope was an important determinant of both the lake‐wide ebullitive fluxes and the fraction of sediment CH 4 production released as bubbles.

A global analysis of ice phenology for 3702 lakes and 1028 reservoirs across the Northern Hemisphere using Sentinel-2 imagery - Doris Domart; Daniel F. Nadeau; Antoine Thiboult; François Anctil; Tadros Ghobrial; Yves T. Prairie; Alexis Bédard-Therrien; Alain Tremblay (Cold Regions Science and Technology, 2024)

The relative importance of seasonality versus regional and network-specific properties in determining the variability of fluvial CO$$_2$$, CH$$_4$$ and dissolved organic carbon across boreal Québec - Ryan H. S. Hutchins; Yves T. Prairie; Paul A. del Giorgio (Aquatic Sciences, 2021)

Niche separation within aerobic methanotrophic bacteria across lakes and its link to methane oxidation rates - Paula C. J. Reis; Shoji D. Thottathil; Clara Ruiz‐González; Yves T. Prairie (Environmental Microbiology, 2020)
Summary Lake methane (CH 4 ) emissions are largely controlled by aerobic methane‐oxidizing bacteria (MOB) which mostly belong to the classes Alpha‐ and Gammaproteobacteria (Alpha‐ and Gamma‐MOB). Despite the known metabolic and ecological differences between the two MOB groups, their main environmental drivers and their relative contribution to CH 4 oxidation rates across lakes remain unknown. Here, we quantified the two MOB groups through CARD‐FISH along the water column of six temperate lakes and during incubations in which we measured ambient CH 4 oxidation rates. We found a clear niche separation of Alpha‐ and Gamma‐MOB across lake water columns, which is mostly driven by oxygen concentration. Gamma‐MOB appears to dominate methanotrophy throughout the water column, but Alpha‐MOB may also be an important player particularly in well‐oxygenated bottom waters. The inclusion of Gamma‐MOB cell abundance improved environmental models of CH 4 oxidation rate, explaining part of the variation that could not be explained by environmental factors alone. Altogether, our results show that MOB composition is linked to CH 4 oxidation rates in lakes and that information on the MOB community can help predict CH 4 oxidation rates and thus emissions from lakes.

Large‐scale biogeography and environmental regulation of methanotrophic bacteria across boreal inland waters - Sophie Crevecoeur; Clara Ruiz‐González; Yves T. Prairie; Paul A. del Giorgio (Molecular Ecology, 2019)
Aerobic methanotrophic bacteria (methanotrophs) use methane as a source of carbon and energy, thereby mitigating net methane emissions from natural sources. Methanotrophs represent a widespread and phylogenetically complex guild, yet the biogeography of this functional group and the factors that explain the taxonomic structure of the methanotrophic assemblage are still poorly understood. Here, we used high‐throughput sequencing of the 16S rRNA gene of the bacterial community to study the methanotrophic community composition and the environmental factors that influence their distribution and relative abundance in a wide range of freshwater habitats, including lakes, streams and rivers across the boreal landscape. Within one region, soil and soil water samples were additionally taken from the surrounding watersheds in order to cover the full terrestrial–aquatic continuum. The composition of methanotrophic communities across the boreal landscape showed only a modest degree of regional differentiation but a strong structuring along the hydrologic continuum from soil to lake communities, regardless of regions. This pattern along the hydrologic continuum was mostly explained by a clear niche differentiation between type I and type II methanotrophs along environmental gradients in pH, and methane concentrations. Our results suggest very different roles of type I and type II methanotrophs within inland waters, the latter likely having a terrestrial source and reflecting passive transport and dilution along the aquatic networks, but this is an unresolved issue that requires further investigation.

No Longer a Paradox: The Interaction Between Physical Transport and Biological Processes Explains the Spatial Distribution of Surface Water Methane Within and Across Lakes - Tonya DelSontro; Paul A. del Giorgio; Yves T. Prairie (Ecosystems, 2018)

Greenhouse Gas Emissions from Freshwater Reservoirs: What Does the Atmosphere See? - Yves T. Prairie; Jukka Alm; Jake Beaulieu; Nathan Barros; Tom Battin; Jonathan Cole; Paul del Giorgio; Tonya DelSontro; Frédéric Guérin; Atle Harby; John Harrison; Sara Mercier-Blais; et al. (Ecosystems, 2018)

The potential of Earth Observation in modelling nutrient loading and water quality in lakes of southern Québec, Canada - Eirini Politi; Yves T. Prairie (Aquatic Sciences, 2018)

Modeling Allochthonous Dissolved Organic Carbon Mineralization Under Variable Hydrologic Regimes in Boreal Lakes - Dominic Vachon; Yves T. Prairie; François Guillemette; Paul A. del Giorgio (Ecosystems, 2017)

Methane ebullition and diffusion from northern ponds and lakes regulated by the interaction between temperature and system productivity - Tonya DelSontro; Lennie Boutet; Annick St‐Pierre; Paul A. del Giorgio; Yves T. Prairie (Limnology and Oceanography, 2016)
Methane (CH 4 ) emissions from aquatic systems should be coupled to CH 4 production, and thus a temperature‐dependent process, yet recent evidence suggests that modeling CH 4 emissions may be more complex due to the biotic and abiotic processes influencing emissions. We studied the magnitude and regulation of two CH 4 pathways—ebullition and diffusion—from 10 shallow ponds and 3 lakes in Québec. Ebullitive fluxes in ponds averaged 4.6 ± 4.1 mmol CH 4 m −2 d −1 , contributing ∼56% to total (diffusive + ebullitive) CH 4 emissions. In lakes, ebullition only occurred in waters 4 m −2 d −1 , and when integrated over the whole lake, contributed only 18% to 22% to total CH 4 emissions. While pond CH 4 fluxes were related to sediment temperature, with ebullition having a stronger dependence than diffusion (Q 10 , 13 vs. 10; activation energies, 168 kJ mol −1 vs. 151 kJ mol −1 ), the temperature dependency of CH 4 fluxes from lakes was absent. Combining data from ponds and lakes shows that the temperature dependency of CH 4 diffusion and ebullition is strongly modulated by system trophic status (as total phosphorus), suggesting that organic substrate limitation dampens the influence of temperature on CH 4 fluxes from oligotrophic systems. Furthermore, a strong phosphorus‐temperature interaction determines the dominant emission pathway, with ebullition disproportionately enhanced. Our results suggest that aquatic CH 4 ebullition is regulated by the interaction between ecosystem productivity and climate, and will constitute an increasingly important component of carbon emissions from northern aquatic systems under climate and environmental change.

The Relative Contribution of Winter Under-Ice and Summer Hypolimnetic CO2 Accumulation to the Annual CO2 Emissions from Northern Lakes - Véronique Ducharme-Riel; Dominic Vachon; Paul A. del Giorgio; Yves T. Prairie (Ecosystems, 2015)

Large‐scale patterns in summer diffusive CH 4 fluxes across boreal lakes, and contribution to diffusive C emissions - Terhi Rasilo; Yves T. Prairie; Paul A. del Giorgio (Global Change Biology, 2015)
Lakes are a major component of boreal landscapes, and whereas lake CO 2 emissions are recognized as a major component of regional C budgets, there is still much uncertainty associated to lake CH 4 fluxes. Here, we present a large‐scale study of the magnitude and regulation of boreal lake summer diffusive CH 4 fluxes, and their contribution to total lake carbon (C) emissions, based on in situ measurements of concentration and fluxes of CH 4 and CO 2 in 224 lakes across a wide range of lake type and environmental gradients in Québec. The diffusive CH 4 flux was highly variable (mean 11.6 ± 26.4 SD mg m −2 d −1 ), and it was positively correlated with temperature and lake nutrient status, and negatively correlated with lake area and colored dissolved organic matter ( CDOM ). The relationship between CH 4 and CO 2 concentrations fluxes was weak, suggesting major differences in their respective sources and/or regulation. For example, increasing water temperature leads to higher CH 4 flux but does not significantly affect CO 2 flux, whereas increasing CDOM concentration leads to higher CO 2 flux but lower CH 4 flux. CH 4 contributed to 8 ± 23% to the total lake C emissions ( CH 4 + CO 2 ), but 18 ± 25% to the total flux in terms of atmospheric warming potential, expressed as CO 2 ‐equivalents. The incorporation of ebullition and plant‐mediated CH 4 fluxes would further increase the importance of lake CH 4 . The average Q 10 of CH 4 flux was 3.7, once other covarying factors were accounted for, but this apparent Q 10 varied with lake morphometry and was higher for shallow lakes. We conclude that global climate change and the resulting shifts in temperature will strongly influence lake CH 4 fluxes across the boreal biome, but these climate effects may be altered by regional patterns in lake morphometry, nutrient status, and browning.

Spatial Heterogeneity of Surface CO2 Fluxes in a Newly Created Eastmain-1 Reservoir in Northern Quebec, Canada - Cristian R. Teodoru; Yves T. Prairie; Paul A. del Giorgio (Ecosystems, 2011)

The relationship between near‐surface turbulence and gas transfer velocity in freshwater systems and its implications for floating chamber measurements of gas exchange - Dominic Vachon; Yves T. Prairie; Jonathan J. Cole (Limnology and Oceanography, 2010)
We performed a series of gas exchange measurements in 12 diverse aquatic systems to develop the direct relationship between near‐surface turbulence and gas transfer velocity. The relationship was log‐linear, explained 78% of the variation in instantaneous gas transfer velocities, and was valid over a range of turbulent energy dissipation rates spanning about two orders of magnitude. Unlike wind‐based relationships, our model is applicable to systems ranging in size from less than 1 km 2 to over 600 km 2 . Gas fluxes measured with our specific model of floating chambers can be grossly overestimated (by up to 1000%), particularly in low‐turbulence conditions. In high‐turbulence regimes, flux overestimation decreases to within 50%. Direct measurements of turbulent energy dissipation rate provide reliable estimation of the associated gas transfer velocity even at short temporal and spatial scales.

Linking forest fires to lake metabolism and carbon dioxide emissions in the boreal region of Northern Québec - DELPHINE MARCHAND; YVES T. PRAIRIE; PAUL A. Del GIORGIO (Global Change Biology, 2009)
Natural fires annually decimate up to 1% of the forested area in the boreal region of Québec, and represent a major structuring force in the region, creating a mosaic of watersheds characterized by large variations in vegetation structure and composition. Here, we investigate the possible connections between this fire‐induced watershed heterogeneity and lake metabolism and CO 2 dynamics. Plankton respiration, and water–air CO 2 fluxes were measured in the epilimnia of 50 lakes, selected to lie within distinct watershed types in terms of postfire terrestrial succession in the boreal region of Northern Québec. Plankton respiration varied widely among lakes (from 21 to 211 μg C L −1 day −1 ), was negatively related to lake area, and positively related to dissolved organic carbon (DOC). All lakes were supersaturated in CO 2 and the resulting carbon (C) flux to the atmosphere (150 to over 3000 mg C m 2 day −1 ) was negatively related to lake area and positively to DOC concentration. CO 2 fluxes were positively related to integrated water column respiration, suggesting a biological component in this flux. Both respiration and CO 2 fluxes were strongly negatively related to years after the last fire in the basin, such that lakes in recently burnt basins had significantly higher C emissions, even after the influence of lake size was removed. No significant differences were found in nutrients, chlorophyll, and DOC between lakes in different basin types, suggesting that the fire‐induced watershed features influence other, more subtle aspects, such as the quality of the organic C reaching lakes. The fire‐induced enhancement of lake organic C mineralization and C emissions represents a long‐term impact that increases the overall C loss from the landscape as the result of fire, but which has never been included in current regional C budgets and future projections. The need to account for this additional fire‐induced C loss becomes critical in the face of predictions of increasing incidence of fire in the circumboreal landscape.

Lakes and reservoirs as regulators of carbon cycling and climate - Lars J. Tranvik; John A. Downing; James B. Cotner; Steven A. Loiselle; Robert G. Striegl; Thomas J. Ballatore; Peter Dillon; Kerri Finlay; Kenneth Fortino; Lesley B. Knoll; Pirkko L. Kortelainen; Tiit Kutser; et al. (Limnology and Oceanography, 2009)
We explore the role of lakes in carbon cycling and global climate, examine the mechanisms influencing carbon pools and transformations in lakes, and discuss how the metabolism of carbon in the inland waters is likely to change in response to climate. Furthermore, we project changes as global climate change in the abundance and spatial distribution of lakes in the biosphere, and we revise the estimate for the global extent of carbon transformation in inland waters. This synthesis demonstrates that the global annual emissions of carbon dioxide from inland waters to the atmosphere are similar in magnitude to the carbon dioxide uptake by the oceans and that the global burial of organic carbon in inland water sediments exceeds organic carbon sequestration on the ocean floor. The role of inland waters in global carbon cycling and climate forcing may be changed by human activities, including construction of impoundments, which accumulate large amounts of carbon in sediments and emit large amounts of methane to the atmosphere. Methane emissions are also expected from lakes on melting permafrost. The synthesis presented here indicates that (1) inland waters constitute a significant component of the global carbon cycle, (2) their contribution to this cycle has significantly changed as a result of human activities, and (3) they will continue to change in response to future climate change causing decreased as well as increased abundance of lakes as well as increases in the number of aquatic impoundments.

PaleoNet: new software for building, evaluating and applying neural network based transfer functions in paleoecology - Julien M. J. Racca; Robert Racca; Reinhard Pienitz; Yves T. Prairie (Journal of Paleolimnology, 2007)

Patterns and regulation of dissolved organic carbon: An analysis of 7,500 widely distributed lakes - Sebastian Sobek; Lars J. Tranvik; Yves T. Prairie; Pirkko Kortelainen; Jonathan J. Cole (Limnology and Oceanography, 2007)
Dissolved organic carbon (DOC) is a key parameter in lakes that can affect numerous features, including microbial metabolism, light climate, acidity, and primary production. In an attempt to understand the factors that regulate DOC in lakes, we assembled a large database (7,514 lakes from 6 continents) of DOC concentrations and other parameters that characterize the conditions in the lakes, the catchment, the soil, and the climate. DOC concentrations were in the range 0.1–332 mg L −1 , and the median was 5.71 mg L −1 . A partial least squares regression explained 48% of the variability in lake DOC and showed that altitude, mean annual runoff, and precipitation were negatively correlated with lake DOC, while conductivity, soil carbon density, and soil C:N ratio were positively related with lake DOC. A multiple linear regression using altitude, mean annual runoff, and soil carbon density as predictors explained 40% of the variability in lake DOC. While lake area and drainage ratio (catchment : lake area) were not correlated to lake DOC in the global data set, these two factors explained significant variation of the residuals of the multiple linear regression model in several regional subsets of data. These results suggest a hierarchical regulation of DOC in lakes, where climatic and topographic characteristics set the possible range of DOC concentrations of a certain region, and catchment and lake properties then regulate the DOC concentration in each individual lake.

Prevalence of Heterotrophy and Atmospheric CO2 Emissions from Aquatic Ecosystems - Carlos M. Duarte; Yves T. Prairie (Ecosystems, 2005)

Fluorescent dissolved organic matter in lakes: Relationships with heterotrophicmetabolism - W. K. Levi Cammack; Jacob Kalff; Yves T. Prairie; Erik M. Smith (Limnology and Oceanography, 2004)
Characterizing dissolved organic matter (DOM) composition remains a major unresolved problem in aquatic ecology and is one of the key impediments to developing a good understanding of DOM production and consumption by heterotrophic bacteria. Fluorescence spectroscopy has been proposed as a promising method for characterizing DOM, but few links have been demonstrated between DOM fluorescence and DOM composition or the processes affected by DOM composition. In 28 southern QueÂbec lakes, tryptophan‐like DOM fluorescence (TFDOM) was found to be a much better descriptor of rates of heterotrophic bacterial metabolism than dissolved organic carbon, describing 52%, 44%, 51%, and 55% of the variability in bacterial production, bacterioplankton respiration, total bacterial carbon consumption, and total plankton community respiration, respectively. In addition, evidence from a series of bacterial regrowth cultures suggests that T‐FDOM represents a product of bacterial activity as well as, to a lesser extent, a bioavailable substrate. Our results instead raise the intriguing possibility that TFDOM concentration reflects a balance between its production and consumption by bacteria. We demonstrate here that fluorescence spectroscopy can be used to identify a highly dynamic fraction of DOM related to bacterial metabolism in lakes.

Apparent and real bias in numerical transfer functions in palaeolimnology - Julien M.J. Racca; Yves T. Prairie (Journal of Paleolimnology, 2004)

Bacterial metabolism and growth efficiency in lakes: The importance of phosphorus availability - Erik M. Smith; Yves T. Prairie (Limnology and Oceanography, 2004)
We investigated bacterial responses to variations in dissolved organic carbon (DOC) and nutrient availability by a comparative analysis of bacterial metabolism in lakes ranging from oligotrophic to eutrophic. Bacterial growth, respiration, and growth efficiency were quantified in lake water dilution cultures performed in 20 lakes located in eastern Quebec, Canada, which varied with respect to both DOC and nutrient concentrations. Intrinsic growth rates of the bacteria ranged from 0.1 to 1.4 d − , bacterial cell‐specific respiration rates ranged from 0.4 to 7.2 fg C cell −1 h −1 , and growth efficiencies ranged from 6.7% to 51.6%. These variations were unrelated to bulk DOC concentrations. Instead, growth rate and efficiency were positively related to total phosphorus concentrations. Specific respiration rate, on the other hand, decreased with increasing phosphorus concentrations, and the magnitude of respiration, on a per‐cell basis, strongly influenced observed growth efficiencies. In a series of substrate enrichment experiments, additions of glucose alone failed to stimulate a response in growth rate, mean cell biovolume, or the potential biomass yield in dilution cultures, but all responded positively to phosphorus additions. Our results show that bacterial metabolism and the fate of DOC input to lake microbial communities are strongly dependent on phosphorus availability, rather than total carbon availability. Extreme oligotrophy appears to place high respiratory demands on the bacterioplankton, resulting in very low bacterial growth efficiencies and consequently greater DOC flow to CO 2 than to biomass available for transfer to higher trophic levels.

Mesozooplankton grazing and primary production: Reply to the comment by Laws - Albert Calbet; Yves T. Prairie (Limnology and Oceanography, 2003)

Separating wheat from chaff: Diatom taxon selection usingan artificial neural network pruning algorithm - Julien M.J. Racca; Matthew Wild; H.J.B. Birks; Yves T. Prairie (Journal of Paleolimnology, 2003)

Diatom-based transfer functions for western Quebec lakes (Abitibi and Haute Mauricie): the possible role of epilimnetic CO2 concentration in influencing diatom assemblages - Aline Philibert; Yves T. Prairie (Journal of Paleolimnology, 2002)

WA-PLS diatom-based pH, TP and DOC inference models from 42 lakes in the Abitibi clay belt area (Québec, Canada) - Mihaela Enache; Yves T. Prairie (Journal of Paleolimnology, 2002)

The summer metabolic balance in the epilimnion of southeastern Quebec lakes - Yves T. Prairie; David F. Bird; Jonathan J. Cole (Limnology and Oceanography, 2002)
On the basis of data collected in Quebec lakes, del Giorgio and Peters (1994) and Carignan et al. (2000) have come to opposite conclusions regarding the metabolic balance between heterotrophy and autotrophy in lakes in general. In the present study, epilimnetic oxygen and carbon dioxide saturation was measured in 33 lakes from the St. Lawrence Lowlands region of Quebec to examine the extent of epilimnetic net heterotrophy (i.e., O 2 :CO 2 balance) in lakes of different characteristics. We found that ~75% of the lakes were undersaturated with oxygen and supersaturated with CO 2 . There was a strong negative relationship between the departures of O 2 and CO 2 from saturation. What has not been noted elsewhere is that oxygen concentrations were negatively related to dissolved organic carbon (DOC) concentration, and, therefore, metabolic gas balances could be predicted from DOC; a value between 4 and 6 mg L −1 DOC corresponds to metabolic equilibrium. Because most of the lakes in del Giorgio and Peters (1994) had DOC concentrations above this threshold and most lakes in Carignan et al. (2000) were below, their apparently contradictory conclusions can be reconciled within a larger general theory. Contrary to studies elsewhere, however, we found that the degree of oxygen undersaturation increased with lake trophic status, expressed either as total phosphorus or nitrogen concentrations.

A comparison between diatom-based pH inference models using Artificial Neural Networks (ANN), Weighted Averaging (WA) and Weighted Averaging Partial Least Squares (WA-PLS) regressions - Julien M.J. Racca; Aline Philibert; Robert Racca; Yves T. Prairie (Journal of Paleolimnology, 2001)

Some aspects of the analysis of size spectra in aquatic ecology - Beatriz Vidondo; Yves T. Prairie; Jose M. Blanco; Carlos M. Duarte (Limnology and Oceanography, 1997)
The established approach to model seston size distributions involves the grouping of particles within logarithmic size classes and the examination of the relationship between density, or normalized biomass, and the characteristic sizes of the classes. Here we examine the distributional basis of the established approach and draw a connection between the biomass size spectrum and the Pareto distribution, a model widely used in other disciplines dealing with size‐structured systems. We provide efficient estimators of the parameters and also suggest that datasets exhibiting significant departures from a smooth power function decline can be adequately modeled using a Pareto type II distribution.

Statistical models for the estimation of net phosphorus sedimentation in lakes - Yves T. Prairie (Aquatic Sciences, 1989)